Simple fancy : a chef's big-flavor recipes for easy weeknight cooking - Santos, Jason (Cook); Hall, Alexandra (Page Street Publishing Co., 2022)
"Impressive dishes without the stress. Turn your kitchen into the swankiest spot in town with these incredible recipes for any day of the week. Known for his mouthwatering food served up with a side of sass on Hell's Kitchen and Bar Rescue, Jason Santos is back with a bang--presenting his latest series of restaurant-quality meals fit for any home cook. With just a few ingredients and easy-to-follow techniques, you can whip up homemade cuisine with all the standout flavors and unique presentation of a professional kitchen"--Page 4 of cover.